2001
DOI: 10.1007/bf01306602
|View full text |Cite
|
Sign up to set email alerts
|

Nonsymbiotic hemoglobins in rice are synthesized during germination and in differentiating cell types

Abstract: Shearman, L.; Mathiesen, M.; Zhou, Y.J.; Arredondo-Peter, R.; Sarath, Gautam; and Klucas, R. V., "Nonsymbiotic hemoglobins in rice are synthesized during germination and in differentiating cell types" (2001 Abstract: Nonsymbiotic hemoglobins (ns-Hbs) previously have been found in monocots and dicots; however, very little is known about the tissue and cell type localization as well as the physiological function(s) of these oxygen-binding proteins. We report the immunodetection and immunolocalization of ns-Hbs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…Non-symbiotic hemoglobin expression has also been detected in germinating seeds of Oryza sativa after imbibition (Ross et al 2001). Hardly any hemoglobin expression is observed in dry barley seeds, but germination results in expression of hemoglobin peaking two to three days after imbibition.…”
Section: Discussionmentioning
confidence: 95%
“…Non-symbiotic hemoglobin expression has also been detected in germinating seeds of Oryza sativa after imbibition (Ross et al 2001). Hardly any hemoglobin expression is observed in dry barley seeds, but germination results in expression of hemoglobin peaking two to three days after imbibition.…”
Section: Discussionmentioning
confidence: 95%
“…However, analysis by confocal microscopy revealed that nsHbs are localized in the cytoplasm of differentiated and differentiating cell types of the developing rice seedling, such as the aleurone, scutellum, root cap cells, sclerenchyma, and tracheary elements. The immunolocalization of nsHbs in the vasculature of root, mesocotyl and leaf tissues, specifically in the xylem, suggests that nsHbs play roles in the metabolism accompanying the differentiation of the xylem (Ross et al, 2001).…”
Section: Localization Of Nshbs and Expression Of Nshb Genes In Plant mentioning
confidence: 98%
“…The endogenous production of NO starts likely not immediately upon but rather shortly after seed imbibition and corresponds to the condition when the internal oxygen becomes depleted. NO production from germinating seeds, similarly to other hypoxic plant tissues, coincides with expression of class-1 nonsymbiotic plant hemoglobin, which appears within 2 h after imbibition and which function was shown to be related to NO scavenging (Taylor et al 1994;Nie and Hill 1997;Duff et al 1998;Hunt et al 2001;Ross et al 2001;). In the reaction, which involves class 1 hemoglobin and corresponding methemoglobin reductase, NO is metabolized in a NADH-dependent reaction which yields nitrate (NO 3 À ) , 2006a, b, reviewed in Gupta et al 2011.…”
Section: Reactive Nitrogen Species In Germinationmentioning
confidence: 91%
“…Class 1 hemoglobin mRNA is absent from dry barley seeds, but becomes detectable within 2 h of imbibition and is detectable in embryo, aleurone, roots, and coleoptile (Andersson et al 1996;Duff et al 1998;Ross et al 2001;Guy et al 2002). In barley and rice, class 1 hemoglobin expression persists for 2-3 days postimbibition and is further enhanced by exposing these tissues to hypoxic (low oxygen) stress (Guy et al 2002).…”
Section: Hemoglobin-dependent Nitric Oxide Turnover In Germinating Seedsmentioning
confidence: 96%
See 1 more Smart Citation